Highly swollen rubbery network in a glassy polymer particle - Pekcan, Onder (Elsevier BV, 1993)
Abstract Fluorescence measurements were carried out on poly(vinyl acetate) particles, prepared by dispersion polymerization in isooctane using a copolymer of 2-ethylhexyl methacrylate [EHMA] and 2-isocyanatoethyl methacrylate as a steric stabilizer. These reactive particles were treated with 2-(1-naphthyl)ethanol to produce particles labelled specifically in the stabilizer phase. Energy transfer experiments were carried out first on the N-labelled particles doped with a hydrocarbon soluble anthracene derivative which dissolved exclusively in the rubbery PEHMA phase. Donor fluorescence decay profiles were measured, and the data were fitted to the Klafter-Blumen model for energy transfer on fractal. The finding that the effective dimensionally d = 2 for this energy transfer process is interpreted in terms of a crossover in a restricted geometry if the PEHMA is present in the form of interconnected long thin (30 A diameter) cylinders. Supporting this idea is our finding that swelling agents for PEHMA, such as hexadecane, are also taken up by the particle from pentane solution. Experiments on these particles give d values that increase with increasing hexadecane until d becomes equal to 3.0. Further swelling measurement were performed with cyclohexane as swelling agent. We found that energy transfer kinetics obeyed a Stern-Volmer type of relation in highly swollen, non-restricted PEHMA phase.